Institutions, corporate governance and capital flows - Rahul Mukherjee (Graduate Institute of International and Development Studies, 2013)
Countries with weaker domestic institutions hold fewer foreign assets and exhibit concentrated corporate ownership. An equilibrium business cycle model of international capital flows with corporate governance frictions between outside investors and insiders explains both phenomena. Investment dynamics under insider control leads relative dividend and labor income for outsiders to be more negatively correlated in countries with weaker institutions. Consequently, outsiders hold more domestic assets to hedge labor income risk. I provide empirical evidence on this hedging demand. Concentrated ownership arises because international diversification through the sale of domestic assets by insiders is penalized by lower stock market valuation.
Keywords: F21; F41; G15; 330; home bias; institutional quality; corporate governance; Kapitalmobilität; Corporate Governance; Institutionelle Infrastruktur; Konjunkturtheorie